(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Split hand is an early clinical sign in amyotrophic lateral sclerosis (ALS) where thenar muscles are substantially more involved than that of hypothenar muscle and Split-hand Index (SI) is the electrophysiological measurement of it. Objective: Our objective was to assess the utility of Split-hand Index in Amyotrophic lateral sclerosis (ALS). Methods: Total 56 study subjects, 28 ALS patients and 28 age & sex matched healthy controls (HCs) were enrolled after satisfying the selection criteria. According to El Escorial diagnostic criteria ALS patients were recruited. Severity and muscle strength state were assessed by ALS functional rating scale-revised (ALSFRS-R) and Medical Research Council (MRC) scores respectively. Then electrophysiology was done to measure SI both in ALS patients and HCs by compound muscle action potential (CMAP) based method. SI was evaluated according to CMAP types in ALS (normal CMAP and reduced CMAP). Collected data were analyzed by IBM SPSS (Statistical Package for Social Sciences) version 26 to observe relation of SI with ALS and its utility. Results: SI was reduced significantly both in normal CMAP and reduced CMAP ALS than Healthy controls (SIReduced CMAP – 1.83±1.30, SINormal CMAP – 5.59±3.72 and SIHCs – 10.57±3.72; p<0.001). SI was positively correlated (r = +0.769, p<0.001) with severity status (ALSFRS-R). SI was also significantly correlated (r= +.893, p<0.001) with status of muscle strength (according to MRC score). Receiver operating characteristic (ROC) curve analysis showed that SI reliably differentiated ALS patients from healthy controls with a cut-off value 5.04 exhibiting 82.1% sensitivity and 85.7% specificity. Conclusion: SI was significantly related with normal CMAP and reduced CMAPALS and reliably differentiated from HCs with high diagnostic accuracy. SI also had strong positive correlation with severity and muscle strength state signifying its role in diagnosis and monitoring ofALS.